Legislação de rotulagem nutricional: instrumento de informação na promoção de escolhas alimentares - Natal-RN - Costa, Sonia Maria Fernandes da (2010)
Resolutions of the Board of numbers 359 and 360, of December 23, 2003, relating to Nutrition Labelling for Packaged Foods, establish quality standards and provide the education activities for health consumption, since one of the factors that enable the selection of healthier foods are the food labels as an important part in nutrition education. This is a descriptive study with a cross-sectional design. To calculate sample size, it was considered a margin of error of 20%, confidence level of 95% and prevalence of 52.5% for verifying nutritional information in a pilot study conducted in 2007. A total of 145 subjects were interviewed, resulting in 371 consumers in Natal, Rio Grande do Norte, Brazil, in order to determine prevalence of consulting nutritional information contained on food labels as a nutritional guideline for consumers and its association with sociodemographic variables as well as identify the intervention measures suggested by intervieweds so that this information can be better used to select healthy foods. Twenty-five of the 69 supermarkets belonging to the Supermarket Association of Rio Grande do Norte (ASSURN) were randomly selected. Data collection relied on interviews and extensive direct observation, using a semi-structured form composed of eight closed questions, some of which were multiple choice, and ten open questions. The chi-square test was performed for statistical analysis, using Statistical Package for Social Sciences (SPSS) 15.0 software. Label information most consulted was: expiry date (91.6%); product brand (49.4%); nutritional information (47.0%); zero trans fat (32.9%); zero sugar content (12.8%); zero fat content (3.0%); rich in fibers (2.7%); whether light or diet (30.4%); list of ingredients (16.8%); whether the product contained gluten or not (4.1%). When asked about the importance of nutritional information, 96.8% of the subjects responded important or very important ; of these 46.6% and 3.8% reported partially or totally understanding the information presented. It was found that 41.6% of the consumers consulted nutritional information for dietary reasons related to nontransmissible chronic diseases and 35.7% to be able to choose healthier foods. The data show a significant association between motivation to choose healthier foods and higher family income and schooling (p<0.0001). The intervention measures mentioned to make nutritional information better understood and used were: information and orientation about nutritional information, provided by qualified professionals in the supermarkets, the commercial establishment or the product manufacturer (73.9%) and media disclosure about the nature, importance and purpose of nutritional information (42.9%). In despite of communication noises the consumers use the nutrition claim for the nutritional guidance, showing association with some demographic variables. However, they desire the implementation of intervention measures that can be contextualized in the political construction of nutrition education to promote healthy food choices